C.A.P.I. Project in the Making: 3D Applications at Poggio Imperiale Between Materiality and Virtual Reality (Poggibonsi, IT) - Bertoldi Stefano (De Gruyter, 2021)
The archaeological project on the hill of Poggio Imperiale began in 1992. From the beginning this project was characterized by intense experimentation with a range of IT applications. During 2014, the University of Siena began a new project focused on the valorisation of archaeological data with the creation of an Open-Air Museum of the Carolingian village, one of the archaeological phases of the settlement. Over the last several years, the use of three-dimensional (3D) data in archaeology has increased exponentially due to the application of photogrammetry to record every stratigraphic unit. This ever-increasing amount of data fostered the development of the C.A.P.I. project (Collina Accessibile di Poggio Imperiale – Accessibility of the Hill of Poggio Imperiale), which involved the construction of a 3D model of the archaeological area of Poggio Imperiale. The project modeled the three main life stages of the hill using 3D computer graphics. Virtual tours can be experienced through PCs, tablets, smartphones, and even virtual reality headsets, offering users a fully immersive experience. However, virtual reality will not be a replacement for the materiality of the archaeological site. On the contrary, it will provide an additional tool to make the site accessible and inclusive to any potential visitor, regardless of physical distance, physical ability, or time zone.